(untitled) (Zaporizhzhia Historical Review, 2021)
The article deals with the theoretical foundations of the development of modern Ukrainian historiography of the New Economic Policy. The author distinguishes the principle priorities and problematic trends of modern investigations of the NEP, and analyzes the current theoretical and methodological approaches, which the Ukrainian historians undertake in their studies of the New Economic policy.